Voluntary cow traffic in AMR : with or without teaser feed at milking - Ratcovich, Elin (SLU/Dept. of Animal Nutrition and Management (until 231231), 2021)
A common automatic milking system (AMS) is the single box AMS, designed for 60 to 70 cows per unit (Bach & Cabrera, 2017), but there is also the automatic milking rotary (AMR; DeLaval Automatic Milking Rotary – AMRTM, Tumba, Sverige) with 24 bails and a higher capacity (Kolbach et al., 2013; Jacobs & Siegford, 2012a). Feed allowance in AMR can lead to advantages and affects cow traffic, both in the barn and in relation to the AMR (Scott et al., 2014; Kolbach et al., 2013). The aim of this study was to investigate the effect of giving teaser feed in AMR during voluntary cow traffic. The aim was also to investigate the effects of different length of adjustment periods in the experimental design. Furthermore, we hypothesized that primiparous cows would adapt faster to the system than multiparous cows and therefore spend less time than multiparous cows in the premilking area. We theorized that results after a longer adjustment period would have less variance and a more reliable outcome than results after a short adjustment period. To examine this, four treatments were implemented: No teaser feed – 1 week adjustment period, Teaser feed – 1 week adjustment period, Teaser feed – 3 weeks adjustment period and No teaser feed – 3 weeks adjustment period. The study was performed in 2018 at the Swedish Livestock Research Centre at Lövsta, Swedish University of Agricultural Sciences, Uppsala and 113 ± 10 cows were included and housed in an insulated naturally ventilated free-stall barn. A trough was installed at the first bail in the AMR to provide the cows with teaser feed (~ 50 g concentrate) when they entered the AMR. All experimental periods, i.e., when data was collected, had the length of one week and followed after every treatment. Data was collected with video recordings and the herd management software DelProTM (DeLaval International AB, Tumba, Sweden) and was used to analyse how fast the cows entered the AMR, how many cows were needed to be fetched by staff and how long time the cows spent in premilking areas. When analysing how fast the cows entered the AMR and how long time they spent in premilking areas, parity and lactation stage was taken into account. To include parity and lactation stage, ~ 30 focal cows were marked. Video observations from 821 entering’s and data from 72 milkings showed that teaser feed made the cows enter the AMR with faster speed and less cows were needed to be fetched by staff than without teaser feed, independent of adjustment period. Results from 464 observations showed that cows spent less time in premilking areas after one week with teaser feed compared to after three weeks without teaser feed. Primiparous cows entered the AMR with faster speed compared to multiparous cows but both primi- and multiparous cows spent the same amount of time in premilking areas, independent of treatment. In retrospect, results regarding adjustment period in this study are weak and should not be used in future research. However, length of adjustment period did not seem to influence the numerical variance but providing teaser feed led to a numerical decrease in variance in data. Overall, this study indicates that offering teaser feed in AMR can be beneficial and have a potential to improve cow traffic.